Worker safety in Designated Microscopy Centers (DMC) and Tuberculosis unit (TU) under Revised National Tuberculosis Control programme (RNTCP) in state of Bihar - Contribution & Role of DTST - Lalitha Krishnappa (Occupational Health and Safety Society of Nepal, 2013)
Damien Foundation India Trust (DFIT), one of the members of International Federation of Anti-Leprosy associations (ILEP) are involved in providing technical and financial support in leprosy and TB control through its projects spread across the country. While support to leprosy control started way back in 1982 through its own project, support to TB control started only in 2003. This study was part of evaluation taken to assess the role of DTST in achieving the planned objectives and to assess the impact of DFIT's involvement in TB control. To assess the current status of worker safety in DMC/TUs of RNTCP centers in state of Bihar and the role and contribution of DTST in ensuring the same. This cross sectional evaluation study was undertaken in randomly selected 8 DMCs/ TUs in rural areas of two districts of Bihar state in 2007. Evaluation was done using pre-tested observational checklist and personal discussions with key personnel. Evaluation included assessment of role & contribution of DTST with respect to infrastructure & resource availability; Training and capacity building; Practice regarding safe disposal of infected materials & worker safety. Most of the civil works was complete in functional DMC/ TUs visited. Sharp pits for sharp disposal were available in only 50% of DMCs/TUs. Staffing position complete to nearly 80%. DTST role in capacity building training, infrastructure availably and monitoring of the programme has been remarkable. However there is a need to emphasis on importance of the worker safety and universal precautions during training. Effective implementation of clearly laid down National guidelines & policy keeping in lieu of the worker safety is the need of the hour when the programme gets streamlined in the general health system.